An Exploratory Study on Hospitality Internship Student’s Satisfaction - Thapa, Amar Bahadur (KIC International Journal of Social Science and Management, 2022)
This study was designed to explore and determine the significant factors that predict internship satisfaction of hospitality and tourism students in the context of Nepal. An exploratory research design was used to identify the factors affecting the satisfaction of intern students in hospitality and tourism students. 399 responses were collected from the colleges of different universities. EFA and regression analysis were applied to students’ responses. Three significant factors, Perceived job, Perceived supervision, and student self-efficacy, where identified, which mainly affect the satisfaction of intern students in hospitality and tourism students. Study results support the service industry to increase the satisfaction of intern students by increasing supervisory activities.